Using Comparison Scenarios to Improve Prenatal Risk Communication. (January 2013) - Pighin, Stefania; Savadori, Lucia; Barilli, Elisa; Rumiati, Rino; Bonalumi, Sara; Ferrari, Maurizio; Cremonesi, Laura
The present research provides empirical evidence of whether communicating the prenatal risk of chromosomal anomalies using comparison scenarios influences women's ability to distinguish between different risk levels. In 2 experiments, participants read a description of a hypothetical woman who was learning of the risk of chromosomal anomaly as a result of a prenatal screening test. Both experiments used a 3 (risk level) × 3 (scenario) full between-subjects design. In accordance with the experimental condition, participants were presented with a low (e.g., 1 in 5390), a medium (e.g., 1 in 770), or a high risk value (e.g., 1 in 110). Such risk values were presented either on their own or along with additional information illustrating a comparison scenario that provided 2 numerical comparison points. Participants were asked to evaluate the risk of chromosomal anomaly. In Experiment 2, participants' numeracy skills were also assessed. Results showed that the use of comparison scenarios results in significant differences in perceived risk across risk levels whereas such differences are not significant without the comparison scenario, but such a technique has differential effects according to participants' capacity to deal with numbers. Although the technique is beneficial for high-numerate participants, it has no effect on low-numerate participants.